Gestão de portfólio de projetos tecnológicos : o caso das instituições brasileiras públicas de pesquisa - Pinheiro, Rafael Sanaiotte (Universidade Federal de São Carlos, 2016)
Institutions are still looking for effective and efficient practices of their portfolio project management (PPM). Similarly, public research laboratories (PRL) are also pursuing this practice. However, these have organizational and institutional factors that differentiate them from private companies. In this way, through a literature review and case studies, developed a theoretical framework to identify and represent the organizational and institutional influence factors in practices and processes of PPM inside Brazilian public research institutions. Based on the five cases realized (a University, an institution with ties to state-owned company and three research institutions linked to Brazilian Government ministries) was able to evaluate the five factors: organizational aspects, institutional environment, identification, selection and priorization of opportunities, administration of resources and development of partnerships. It could be listed as findings of this thesis: the low adoption of PPM practices in national research institutions, the influence of public policy in the development of research activities of these institutions, and the need for a better development of managerial practices of administrative activities. Only two institutions studied have structured procedures to select, prioritize, track and monitor their projects portfolios.
Keywords: Gestão de portfólio de projetos; Institutos de pesquisa; Instituições públicas; Aspectos organizacionais; Ambiente institucional; Project portfolio management; Research institutes; Public institutions; Organizational aspects; Institutional environment; ENGENHARIAS::ENGENHARIA DE PRODUCAO